Vision Based Approach to Sign Language Recognition - Himanshu Gupta; Aniruddh Ramjiwal; Jasmin T. Jose (Institute of Advanced Engineering and Science, 2018)
We propose an algorithm for automatically recognizing some certain amount of gestures from hand movements to help deaf and dumb and hard hearing people. Hand gesture recognition is quite a challenging problem in its form. We have considered a fixed set of manual commands and a specific environment, and develop a effective, procedure for gesture recognition. Our approach contains steps for segmenting the hand region, locating the fingers, and finally classifying the gesture which in general terms means detecting, tracking and recognising. The algorithm is non-changing to rotations, translations and scale of the hand. We will be demonstrating the effectiveness of the technique on real imagery.